2012
DOI: 10.1111/j.1467-9922.2012.00731.x
|View full text |Cite
|
Sign up to set email alerts
|

Age Effects in a Study Abroad Context: Children and Adults Studying Abroad and at Home

Abstract: This study examines the effects of learning context and age on second language development by comparing the language gains, measured in terms of oral and written fluency, lexical and syntactic complexity, and accuracy, experienced by four groups of learners of English: children in a study abroad setting, children in their at‐home school, adults in a study abroad setting, and adults in their at‐home university. Results show that the study abroad context was superior to the at‐home context, and more advantageous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
90
5

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 90 publications
(103 citation statements)
references
References 79 publications
(102 reference statements)
8
90
5
Order By: Relevance
“…These results confirm the superiority of the SA context over the AH context reported by a previous study (Llanes & Muñoz, ), also for perceived FA. That study showed that the SA context was more beneficial for L2 improvement than the AH context, in terms of the participants' oral skills (measured by a set of fluency, complexity, and accuracy measures).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These results confirm the superiority of the SA context over the AH context reported by a previous study (Llanes & Muñoz, ), also for perceived FA. That study showed that the SA context was more beneficial for L2 improvement than the AH context, in terms of the participants' oral skills (measured by a set of fluency, complexity, and accuracy measures).…”
Section: Discussionsupporting
confidence: 92%
“…Several recent studies have explored the potential multiple effects of study abroad (SA) experiences on the acquisition of a second language (L2) (Llanes & Muñoz, ; Serrano, Tragant, & Llanes, ; Trenchs–Parera, ). However, these studies have mainly focused on specific areas such as fluency, grammar, writing, vocabulary, and pragmatics, whereas other L2 areas such as reading, listening, and phonological skills have been underinvestigated.…”
mentioning
confidence: 99%
“…In contrast, to study the relationship between age and the learning context, Llanes and Muñoz (2012) conducted a comparative study with seventythree children (of whom thirty-nine studied abroad between two to three months, and thirty-four in their own country) and sixty-six adults (forty-six studied abroad between two to three months, and twenty in their own country). The results displayed that, generally, study abroad promotes fluency in both children and adults.…”
Section: Effects On Lexical Knowledge and Writing Abilitiesmentioning
confidence: 99%
“…In the last decade, much research has been carried out with the aim to analyze the role of individual differences during study abroad such as learning strategies (Adams, 2006;Lafford, 2004;Paige, Cohen, & Shively, 2004), students' beliefs (Amuzie & Winke, 2009;Tanaka & Ellis, 2003), and age (Llanes & Muñoz, 2012).…”
Section: Effects On Lexical Knowledge and Writing Abilitiesmentioning
confidence: 99%
See 1 more Smart Citation